2020
DOI: 10.1111/pce.13869
|View full text |Cite
|
Sign up to set email alerts
|

Decoding ABA and osmostress signalling in plants from an evolutionary point of view

Abstract: The plant hormone abscisic acid (ABA) is fundamental for land plant adaptation to water-limited conditions. Osmostress, such as drought, induces ABA accumulation in angiosperms, triggering physiological responses such as stomata closure. The core components of angiosperm ABA signalling are soluble ABA receptors, group A protein phosphatase type 2C and SNF1-related protein kinase2 (SnRK2). ABA also has various functions in non-angiosperms, however, suggesting that its role in adaptation to land may not have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 153 publications
0
49
0
Order By: Relevance
“…Likewise, genomic and genetic evidence also strongly suggests that the core ABA signaling pathway was already present in the common ancestor of land plants (Khandelwal et al, 2010; Bowman et al, 2017; Eklund et al, 2018; Sun et al, 2019; Komatsu et al, 2020). It was proposed that ABA functions are a major adaptation in early land plants, enabling them to balance protection against osmostress and growth for successful colonization of terrestrial environments (Khandelwal et al, 2010; Takezawa et al, 2011; Eklund et al, 2018; Sun et al, 2019; Komatsu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, genomic and genetic evidence also strongly suggests that the core ABA signaling pathway was already present in the common ancestor of land plants (Khandelwal et al, 2010; Bowman et al, 2017; Eklund et al, 2018; Sun et al, 2019; Komatsu et al, 2020). It was proposed that ABA functions are a major adaptation in early land plants, enabling them to balance protection against osmostress and growth for successful colonization of terrestrial environments (Khandelwal et al, 2010; Takezawa et al, 2011; Eklund et al, 2018; Sun et al, 2019; Komatsu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and genomic analyses have shown that de novo ABA biosynthesis via the carotenoid pathway is likely functionally conserved in land plants, which are considered to have descended from an ancestral form of aquatic algae (Hauser et al, 2011; Takezawa et al, 2011; Takezawa et al, 2015; Bowman et al, 2017; Komatsu et al, 2020). Likewise, genomic and genetic evidence also strongly suggests that the core ABA signaling pathway was already present in the common ancestor of land plants (Khandelwal et al, 2010; Bowman et al, 2017; Eklund et al, 2018; Sun et al, 2019; Komatsu et al, 2020). It was proposed that ABA functions are a major adaptation in early land plants, enabling them to balance protection against osmostress and growth for successful colonization of terrestrial environments (Khandelwal et al, 2010; Takezawa et al, 2011; Eklund et al, 2018; Sun et al, 2019; Komatsu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subclass III SnRK2s are activated in ABA-deficient and ABA-insensitive mutants, suggesting that SnRK2s can be activated by upstream kinases in an ABA-independent manner under drought stress [ 17 , 27 , 41 , 42 ]. B-type MPK KINASE KINASE (MAPKKK) Raf-like kinases have been shown to directly regulate the activity of SnRK2s under osmotic stress [ 12 , 43 , 44 , 45 ]. An ABA-insensitive Physcomitrella patens mutant was isolated by a forward genetic approach and was shown to have a mutation in a gene for ABA AND ABIOTIC STRESS-RESPONSIVE RAF-LIKE KINASE/ABA NON-RESPONSIVE (ARK/ANR), one of the B3-MAPKKK Raf-like kinases [ 46 , 47 ].…”
Section: Importance Of Aba-dependent Responses Under Drought Stressmentioning
confidence: 99%
“…Rice ABA signaling is now understood well and it starts with ABA binding with its receptor (OsPYR1/PYL/RCAR) complex leading to the inhibition of protein phosphatase 2C (PP2C) mediated inactivation of sucrose nonfermenting 1-related protein kinase 2s (SnRK2s). This, in turn, activates ABA-responsive transcription factors like bZIPs to execute a downstream response to stress adaptation, including drought [ 11 , 12 ]. ABA levels are tightly regulated in response to development and stresses [ 13 ].…”
Section: Transgenic Approach For Improving Rice Drought Tolerancementioning
confidence: 99%